PROMOTING CHARACTER VALUES FOR EFL STUDENTS THROUGH DIGITAL LEARNING MATERIAL - Dewi Suriyani Djamdjuri; Nanik Retnowati; Herawati Kartadimadja (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2022)
Incorporating character education through digital learning materials is one of the attempts to establish conducive circumstances for learners to study English while being familiar with the concepts of character that can often be perceived through Islamic learning materials. Clearly, the majority of Indonesians are Muslims, and they require educational materials that reflect their Muslim lifestyle. These learning experiences help students understand the information more easily, allowing them to improve their English skills. For these purposes, this study aims to observe how the students’ responses reflect their understandings of the integrated principles of character values in the English learning materials. Using a descriptive qualitative approach with a survey method, the research was conducted at the English Education program in the Faculty of Teachers' Training and Education, Bogor Ibn Khaldun University. Two classes, each consisting of 20 students, were treated to Islamic learning materials in the form of digital books. To get the data, 10 students were addressed with a set of interviews. As a result of the study, it was found that the students' understandings of integrated character values are largely concerned with six dimensions: religiosity, honesty, independence, curiosity, friendliness, and responsibility. The students not only comprehended the character qualities, but they were also able to apply them in real life. Furthermore, the use of digital books as learning resources attracted the students' curiosity, and they seemed to appreciate it. Students believed that learning content through a digital book was efficient and could contribute to the improvement of their language skills.